New Insights Into the Nature of Interspecific Hybrid Sterility in Rice - Li, Jing; Zhou, Jiawu; Zhang, Yu; Yang, Ying; Pu, Qiuhong; Tao, Dayun (Frontiers in Plant Science, 2020)
Interspecific and intersubspecific hybrid sterility is a common phenomenon of postzygotic reproductive isolation in rice, which is an indicator of speciation involved in the formation of new species or subspecies, and significantly hampers the utilization of the favorable genes from distant parents for cultivated rice improvement. The Oryza Genus including 8 species with the same AA genome is a model plant to study the nature of hybrid sterility, the relationship between hybrid sterility and speciation. Hybrid sterility in rice is mostly controlled by nuclear genes and more than 50 sterility loci were genetically identified, among which 10 hybrid sterility genes (seats) were cloned and characterized at molecular level. A comparison of the mapping results for all sterility genes reported, indicated that some sterility genes from different species should be allelic to each other. With the further research, the interaction between the multiple alleles at the S-locus caused the various results. One hypothesis for this important phenomenon is that the allelic genes are orthologous genes, which exist in the ancient ancestors. When the ancestor drifted to the different Continents, genetic divergence occurred because of adaptation, selection and isolation among them and as the result the various alleles appeared; hence, interspecific hybrid sterility was mainly controlled by a few orthologous loci with different alleles. This hypothesis was supported by the molecular characterization of hybrid sterility genes from S1, S5, Sa, qHMS7 and S27. It can be deduced further that the allelic interaction and non-allelic interaction among different loci are the major genetic base for the interspecific hybrid sterility between O. sativa and its AA genome relatives, and the same is true for intersubspecific hybrid sterility in O. sativa. Thus, it is necessary to raise the near-isogenic lines with various alleles (haplotypes) and pyramided different loci in the same genetic background for the aim of studying allelic interaction and non-allelic interaction among different hybrid sterility loci in interspecific, intersubspecific, and intraspecific of the AA genome species and using the pyramiding lines as bridge parents to overcome the hybrid sterility for breeding purpose.